The impact of apprenticeship training on personality traits: An instrumental variable approach - Thomas Bolli; Stefanie Hof (ETH Zurich, KOF Swiss Economic Institute, 2014)
This paper analyzes how apprenticeship training, i.e., work-based secondary education, affects personality traits compared to full-time school-based vocational or general education. Employing an instrumental variable approach that exploits the regional differences in the relative weight of school- and work-based secondary education across Switzerland and Europe, we determine that apprenticeship training reduces neuroticism and increases agreeableness and conscientiousness, while openness and extraversion remain unaffected. These results validate the socializing function of work-based education. However, heterogeneous treatment effects are found, indicating positive effects for students with less favorable personality traits but insignificant or even reducing effects in the case of extraversion for those with already high values in personality traits.
Keywords: C26; D01; I20; J24; 330; Apprenticeship; work-based education; VET; Big Five; personality traits